A two‒dimensional IR spectroscopic (2D‒IR) simulation of protein conformational changes. Issue 1 (2004) - Arrondo Arrondo, José Luis R. José Luis R.; Iloro Iloro, Ibon Ibon; Aguirre Aguirre, Julián Julián; Goñi Goñi, Félix M. Félix M.
Abstract : Two‒dimensional IR correlation spectroscopy (2D‒IR) is a novel method that provides the analysis of infrared spectra with the capacity to differentiate overlapping peaks and to distinguish between in‒phase and out‒of‒phase spectral responses. Artificial spectra originated from protein amide I band component parameters have been used to study their variation in the correlation maps. Using spectra composed of one, two or three Gaussian peaks, behaviour patterns of the bands in the synchronous and asynchronous maps have been originated, with changes in intensity, band position and bandwidth. Intensity changes produce high‒intensity spots in the synchronous spectra, whereas only noise is observed in the asynchronous spectra. Band shifting originates more complex patterns. In synchronous spectra, several spots are generated at the beginning and at the end of the shifting band. Also, characteristic asynchronous spectra with butterfly‒like shapes are formed showing the trajectory of the shift. Finally, synchronous maps corresponding to band broadening reveal several spots at peak inflection points, related to the zones with higher intensity variation. The asynchronous spectra are very complex but they follow a characteristic symmetric pattern. Furthermore, examples of maps obtained from polypeptides and proteins using temperature as the perturbing factor are interpreted in terms of the patterns obtained from artificial bands.